Finite Element Analysis of Flexsplines of Cone-beam Oral CT Harmonic Reducers - Wang Zhijie; Song Weidong; Zhang Yue; Guan Haoran; Zhang Fengshou (Jixie chuandong)
The cone-beam oral CT requires high transmission accuracy, and harmonic reducers with smooth operation, high precision efficiency and safety factor are mostly used. Its flexspline is prone to failure due to periodic deformation under alternating load when rotating. The tooth profile of the flexspline is designed, modeled by SolidWorks, and imported into the Ansys Workbench for the static analysis, modal analysis, and transient dynamic analysis. The results show that the flexural strain is mainly located at the long and short axes of the wave generator, and the axial strain decreases gradually along the cylinder. The maximum stress is located at the contact between the wave generator and the flexspline, and the maximum stress is located at the connection between the tooth root and the cylinder during the transient dynamic analysis. At the same time, the stress and strain of the flexspline are also affected by tooth width, barrel length and barrel thickness.